1991
DOI: 10.1164/ajrccm/143.1.66
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence ofMycobacterium aviumComplex in Respiratory Specimens from AIDS and Non-AIDS Patients in a San Francisco Hospital

Abstract: Over the past several years there has been a large increase in the recovery of Mycobacterium avium complex (MAC) isolates from respiratory specimens submitted to the clinical laboratory at San Francisco General Hospital (SFGH). This increase in MAC recovery correlates with an increase in the number of cases of acquired immunodeficiency syndrome (AIDS) in the community. Although it is well known that MAC is often isolated from patients with AIDS, the isolation of MAC from respiratory specimens is often attribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

1992
1992
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 4 publications
1
9
0
Order By: Relevance
“…Basic characteristics (frequency) of NTM recovery of our CF patients (11.0% single, 5.5% repeated) were comparable to previous reports on CF patients (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19).5% single, 1-8% repeated) [1,8,10,13,20,21,22,28,31]. Also NTM species isolated from CF patients resembled previous reports [1,10,13,20,21,22,23,31].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Basic characteristics (frequency) of NTM recovery of our CF patients (11.0% single, 5.5% repeated) were comparable to previous reports on CF patients (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19).5% single, 1-8% repeated) [1,8,10,13,20,21,22,28,31]. Also NTM species isolated from CF patients resembled previous reports [1,10,13,20,21,22,23,31].…”
Section: Discussionsupporting
confidence: 89%
“…To assess the significance of detecting environmental fac- Table 2 Prevalence, incidence, and frequency of NTM in CF patients and non-CF patients [95% CI exact binomial 95% confidence interval, Frequency ''period prevalence'', proportion of the study population that were cases at any time within the study period, Incidence new cases divided by the number of study population at risk (total study population minus prevalent cases), NS not significant (P>0.05), NTM nontuberculous mycobacteria, NTM>1 isolation of the same NTM species in the same patient in at least two samples, Prevalence ''point prevalence'' on study entry, RR relative risk with Taylor series 95% confidence limits (CL)] [12,17]. Age of the patients seems to be an important predisposing factor, as O'Brien et al [19] reported that 88% of patients with pulmonary M. avium complex disease (as defined therein) were over 45 years of age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Non tuberculous mycobacteria belonging to the Mycobacterium avium complex (MAC) have been increasingly recognized as an important group of organisms causing severe opportunistic infection in patients with acquired immunodeficiency syndrome (AIDS) in the United States (Kiehn et al 1985, Young et al 1986, Horsburgh & Selik 1989, Nassos et al 1991, Havlik et al 1992, Europe (Yates et al 1986, Wickman 1986, Grange et al 1990) and Australia (Dawson 1990). In Brazil an increase in the frequency of M. avium complex infections has also been found associated with AIDS patients (Barreto et al 1993, Landgraf et al 1994.…”
mentioning
confidence: 99%
“…In the United States, 25 to 50% of AIDS patients develop symptomatic disease due to MAC and the HIV epidemic has led to an overall rise in MAC disease incidence (Nassos et al 1991). In south-east England the number of isolates of MAC associated with symptomatic disease in HIV-positive patients has increased from 13 in 1987 to 161 in 1993 (Yates et al 1993) (Fig.…”
Section: Incidence Of Macmentioning
confidence: 99%